Peran kepemimpinan transformasional dalam meningkatkan kinerja karyawan - Edi Muhammad Abduh Alhamidi (Jurnal Integrasi Sumber Daya Manusia, 2022)
Leadership is one of the locomotives for organizational growth. Transformational leadership is a popular leadership style applied in various organizations because it can move employees towards optimal performance and benefit the organization. This research method uses the PLS-SEM technique with data processing using SmartPLS. The samples used were 72 hotel employees in the Cinangka area, Serang Regency. The results show that inspirational motivation can improve employee performance, idealized influence has a positive influence on improving employee performance, individualized consideration has a positive and significant impact on contributing to employee performance improvement, and intellectual stimulation has a positive and significant effect on employee performance.